A duration analysis of housing construction times: Evidence on the role of option values, public involvement and stalled sites - Lars Brugman; Jan Rouwendal (Tinbergen Institute, 2024)
This paperinvestigates the duration of housing construction projects in the Netherlands. We utilize comprehensive data from the Dutch Land Registry for the period 2013-2022 to investigate the importance of municipal land ownership, building plot price changes, construction costs, development inside areas that are already built-up and competition. The construction process covers the time between issuance of building permits and completion of the project, which can be split in a preparation and construction phase. We find that municipal involvement in projects speeds them up significantly, while increasing building plot prices and especially construction costs have a delaying effect. Construction inside already built-up areas fastens the preparation and slows down actual construction, with an significant net delaying effect on the total duration. Competition decreases the time needed for construction. Our results lend support to real option theory and indicate differences in the objections of private firms and local authorities.
Keywords: R3; R5; D2; 330; housing construction; housing supply; land use planning